Assist your personal wellness and selfcare with artificial intelligence buddy: alive / Zuhal Hussein, Che Nur Asmani Amirah Che Mohd Nawi and Che Nur Asmani Amira Che Mohd Nawi - Hussein, Zuhal; Che Mohd Nawi, Che Nur Asmani Amirah; Che Mohd Nawi, Che Nur Asmani Amira (Universiti Teknologi MARA, Negeri Sembilan, 2023)
In today’s swift world, maintaining personal wellness has become an extreme concern. Artificial intelligence (AI) has emerged as a powerful ally in this endeavour, offering innovative solution through mobile health applications. This mobile health application diary ‘Alive’ explores the concept of AL buddy, a mobile health application designed to assist individuals in enhancing their personal wellness and self-care routines. ‘Alive’ diary leverages the capabilities of AI to provide personalized support across various functions of personal wellness, including mental well-being, physical health, and lifestyle management. Through the artificial intelligence-driven algorithms, the mobile health application analyses user data, such as sleep patterns, food intake, daily activities levels, diet preferences, stress indicators, and meditation, to provide tailored recommendations and insights. The key features of Alive diary include real-time health monitoring through wearable devices, such as smartphone and smartwatches, and mental health support through AI chatbots, medication management reminder, sleep pattern, health management such as exercise, healthy food, social support, and access to telehealth services. The applications also aid in health behavioural change and promote healthy lifestyle. In addition, Alive diary buddy empowers users to customize their sleep pattern, fitness routines, access to healthcare information, have to-do list, and other interfaces with engaging design. It optimizes the potential of the application as a comprehensive tool for encouraging personal wellness and self-care, bridging the gap between individuals and healthcare resources. By tackling the potential of Alive diary buddy, this mobile health applications paves the way for a healthier, more proactive, more informed, and well engaged approach to selfcare in the digital age, the era of digital health.